Review of neurodevelopmental disorders in patients with HNF1B gene variations - Nittel, Clara Marie; Dobelke, Frederike; König, Jens; Konrad, Martin; Becker, Katja; Kamp-Becker, Inge; Weber, Stefanie; , for the NEOCYST consortium (Frontiers in Pediatrics, 2023)
This review investigates the association between neurodevelopmental disorders (NDD) and variations of the gene HNF1B. Heterozygous intragenetic mutations or heterozygous gene deletions (17q12 microdeletion syndrome) of HNF1B are the cause of a multi-system developmental disorder, termed renal cysts and diabetes syndrome (RCAD). Several studies suggest that in general, patients with genetic variation of HNF1B have an elevated risk for additional neurodevelopmental disorders, especially autism spectrum disorder (ASD) but a comprehensive assessment is yet missing. This review provides an overview including all available studies of patients with HNF1B mutation or deletion with comorbid NDD with respect to the prevalence of NDDs and in how they differ between patients with an intragenic mutation or 17q12 microdeletion. A total of 31 studies was identified, comprising 695 patients with variations in HNF1B, (17q12 microdeletion N = 416, mutation N = 279). Main results include that NDDs are present in both groups (17q12 microdeletion 25.2% vs. mutation 6.8%, respectively) but that patients with 17q12 microdeletions presented more frequently with any NDDs and especially with learning difficulties compared to patients with a mutation of HNF1B. The observed prevalence of NDDs in patients with HNF1B variations seems to be higher than in the general population, but the validity of the estimated prevalence must be deemed insufficient. This review shows that systematical research of NDDs in patients with HNF1B mutations or deletions is lacking. Further studies regarding neuropsychological characteristics of both groups are needed. NDDs might be a concomitant of HFN1B-related disease and should be considered in clinical routine and scientific reports.